Compiling a Comparable Ad Hoc Corpus of Birth Certificates and Marriage Certificates in Spanish and English: A Valuable Resource for Legal Translation [Compilación de Un Corpus Ad Hoc Comparable de Certificados de Nacimiento y Matrimonio en Español y en Inglés: Un Recurso Valioso Para la Traducción Jurídica] - Morales-Santibanez, A; Contreras-Torregrosa, M (Universidad de Granada, 2020)
This paper highlights the need of compiling both monolingual and bilingual comparable ad hoc corpora consisting of official documents in Spanish and English in order to determine terminological and phraseological features of specific legal genres and to have access to specialized concepts within the relevant legal framework. Different types of corpora are characterized and an example of analysis that can be helpful for the translation process of legal texts is included. Particularly, the paper stresses the value of the use of corpora in the search of Spanish-English equivalences for birth and marriage certificates, which were analyzed regarding their internal and external elements. © 2020 Universidad de Granada. All rights reserved.